Fundamental Principles and Activities in Tackling Corruption in the Republic of Kazakhstan - NURMAGANBET, Ermek Talantuly; IZBASOVA, Asel Boranovna; KUANALIEVA, Guldana Amangeldiyevna; KONYSBAY, Bakytkul Menlenkyzy (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
In this paper authors analysed the theoretical and practical issues deals with anti-corruption drive of the Republic of Kazakhstan. Here was indicated that one of the causes of corruption are economic reasons and patterns of problems of commodity and money fetishism. During this study was relevant such methods of analysis: structural, logical, historical and social, analysis, deduction and induction, both scientific methods of comparative-legal, logical-legal and historical-legal analysis. Authors indicated the strong connections between operative search, crime period and anticorruption activities with fact that society is almost powerless to resist the growing negative processes. Concluded that educational methods of conduct the anti-corruption drive are just as important as law and governmental methods. Anyways, modernization of normative base of the Republic of Kazakhstan concerning to fight with organized corruption and crime, improving of quick research and conduct crime business law, also developing of system of using and taking as an evidence corruption crime.